Relatório de Estágio Profissional "Ser Professor: Saber dar para receber - Daniela Madalena Brito dos Reis (2017)
This document is the final result from the Professional Internship made in the framework of the 2nd Cycle of The Physical Education Teaching program, at a Basic and Secondary School levels, inserted in the Masters Degree of the Faculty of Sport of the University of Porto. This intern took place in basic and secondy Tomás de Borba School and it took the all year. The goal with this project is insert the student in a real environment, analyzing the supervised practice of the intern on his activities.This report describes and shows all the activities embraced by the intern student, as well as the strategies she founds, difficulties and acquired knowledge. The studen doesn't walk alone, and there was a guidance of a school professor and a collegede guidance. This document is organized in 5 main chapters with all the information of the background and also included the feelings, emotions, solutions and problems.The first chapter is a short introduction, the second talk about the student's background, the third describes the social environment, the forth aproach the teaching activity and the final one is a short conclusion about all this way to be